Cascade SN2′–SNAr, Elimination, and 1, 5‐Hydride Shift Reactions by Acetylacetone/Acetoacetic Esters: Synthesis of 9, 10‐Dihydroacridines. Issue 29 (28th September 2016) - Gupta, Tanu; Bharadwaj, Kishor Chandra; Singh, Radhey M.
Abstract : A reaction involving the use of acetylacetone/methyl acetoacetate and Morita–Baylis–Hillman acetates for the efficient, one‐pot, metal‐free synthesis of 9, 10‐dihydroacridines at room temperature was developed. The cascade of reactions involved sequential SN 2′–SN Ar reactions, elimination, and reduction through ketene generation and hydride transfer. Evidence for hydride shift via a ketene intermediate was also discussed. Abstract : A metal‐free synthesis of 9, 10‐dihydroacridines at room temperature is developed by using Morita–Baylis–Hillman acetates and acetylacetone/methyl acetoacetate. Evidence of a ketene intermediate is also explored.